Improving Students’ Reading Comprehension of Narrative Text Through Directed Reading-Thinking Activity Strategy - Ahmad Fawahid; Y Gatot Sutapa Yuliana; Luwandi Suhartono (Acitya: Journal of Teaching and Education, 2023)
This study aim was to find out how directed reading-thinking activity strategy could improve students’ reading comprehension of narrative text. The directed reading-thinking activity strategy was applied to teach the ninth grade students of SMPS Awaluddin in the academic year of 2021/2022. This study was a classroom action research. The research findings showed that the students paid attention to the teacher’s explanation, the students were very active and brave to ask the teacher, looked enthusiastic and understood the reading comprehension of narrative text through directed reading-thinking activity strategy. It also was proven by the students’ individual reading test, in which their scores got increase because many students’ individual score got 72 until 84 which included good category, and two students got 88 until 92 as excellent category. Therefore, it can be concluded that directed reading- thinking activity strategy successfully improved the students’ reading comprehension of narrative text. The researcher hopes this strategy is used by the teachers in teaching reading comprehension.